Inovasi Suplemen Pakan Sakura Blok Plus untuk Meningkatkan Produksi Susu Sapi Perah - Amir Husaini Karim Amrullah; Dadang Suherman; Jarmuji Jarmuji (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2019)
Giving sakura block plus that contain katuk leaf and turmeric flour are expected to increase the production of milk from dairy cow in Sumber Mulya livestock group. Community service activities are carried out through several stages: socialization, training, demonstration plots, and field tests. Socialization aims to provide an understanding of the purpose and objectives of the activity. The training has several objectives, namely the introduction of sakura block plus supplements, understanding the benefits of sakura block plus supplements for dairy cattle, materials and equipment used, and practices. Making sakura block plus begins with weighing ingredients, then mixed them until blended. Then, heat the brown sugar that has been mixed with 20% water. After that, mix the ingredients with brown sugar. Next, sakura block plus is pressed by presses tool. The last stage is wrapping it using plastic wrap. The demonstration plot and field test were conducted for three months and using three dairy cattle. The forage consumption of dairy cows used in demonstration plots ranges from 40-45 kg/head/day. Milk production in Sumber Mulya livestock group is 10.28 liters/head/day. The use of sakura blok can increase milk production 2 until 3 liters/head/day. The average milk production after using sakura block plus can reach 13 liters/head/day.Keywords: katuk leaf; livestock group; milk; suplement.